2007
DOI: 10.1063/1.2746047
|View full text |Cite
|
Sign up to set email alerts
|

The stabilizing effect of streaks on Tollmien-Schlichting and oblique waves: A parametric study

Abstract: The stabilizing effect of finite amplitude streaks on the linear growth of unstable perturbations ͓Tollmien-Schlichting ͑TS͒ and oblique waves͔ is numerically investigated by means of the nonlinear parabolized stability equations. We have found that for stabilization of a TS-wave, there exists an "optimal" spanwise spacing of the streaks. These streaks reach their maximum amplitudes close to the first neutral point of the TS-wave and induce the largest distortion of the mean flow in the unstable region of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…This is consistent with the behaviour of the optimal streak (Cossu & Brandt 2004;Bagheri & Hanifi 2007;Schlatter et al 2011), steady roughness or vortex generator streaks (Fransson et al 2005a(Fransson et al , 2006Shahinfar et al 2012), and Klebanoff streaks (Arnal & Juillen 1978;Boiko et al 1994;Watmuff 1998). However, it contrasts the results of Vaughan & Zaki (2011) for steady streaks generated from the free stream with a Squire mode that increased TS-wave growth rates at low streak amplitudes.…”
Section: Streak Amplitudesupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with the behaviour of the optimal streak (Cossu & Brandt 2004;Bagheri & Hanifi 2007;Schlatter et al 2011), steady roughness or vortex generator streaks (Fransson et al 2005a(Fransson et al , 2006Shahinfar et al 2012), and Klebanoff streaks (Arnal & Juillen 1978;Boiko et al 1994;Watmuff 1998). However, it contrasts the results of Vaughan & Zaki (2011) for steady streaks generated from the free stream with a Squire mode that increased TS-wave growth rates at low streak amplitudes.…”
Section: Streak Amplitudesupporting
confidence: 86%
“…Computations (Cossu & Brandt 2002) and stability theory (Cossu & Brandt 2004;Bagheri & Hanifi 2007) have shown that the steady optimal streak (Andersson, Berggren & Henningson 1999;Luchini 2000) reduces TS-wave growth rates. Streaks forced by roughness elements (Fransson et al 2005a;Gürün 2006) or miniature vortex generators have also shown reduced TS-wave growth, and sometimes transition delay (Fransson et al 2006;Shahinfar et al 2012;Shahinfar, Sattarzadeh & Fransson 2014).…”
Section: Observations Of Boundary-layer Spanwise Variationmentioning
confidence: 99%
“…This amplitude is well below published thresholds for streak secondary instability in a zero pressure gradient 3,19 and is likely to have a minimal affect on TS growth. 6,7 The strength and amplitude measures are not linearly related for the streaks considered. The ratio δ*/A varies with streamwise position and streak strength, Initial CFD attempts failed to reproduce the case4U streak using a free-stream wake composed only of U and W components that matched the experimental data.…”
Section: A Case2t: Wire In the Test-sectionmentioning
confidence: 99%
“…Most recent computational studies use the Optimal streak 1, 2 at nonlinear amplitudes. [3][4][5][6][7][8] Experimental studies have used roughness elements, [9][10][11] micro-wings, [12][13][14] or more recently vortex generators 15,16 to create streaks. While these studies have produced streaks with some comparable characteristics to Klebanoff streaks, the disturbance mechanism does not model wind tunnel settling chamber screens which have been empirically linked to Klebanoff streaks.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the boundary layer with finite amplitude streaky distortions has been deeply analyzed 4,5,2 , and experimentally tested 6,7 , detecting that the increase of the amplitude of the streaks can have an stabilizing effect in the Blasius boundary layer, delaying the onset of turbulence. The limit of this effect and streak stability characteristics are far from clear 1,15 , and they probably depend not only on the magnitude of its spanwise modulation but also on how the streaks are generated.…”
Section: Introductionmentioning
confidence: 99%